Waterspace Planning and the River Thames in London. (November 2015) - Pinch, Philip
Abstract : London is a city that stands, for many, at the pinnacle of neoliberal global urbanization and market-led residential and commercial property investment. Its iconic River Thames has become a focus for much of this development, particularly of luxury apartments. There has been an emerging sense that the river increasingly has been captured by a specific set of class interests and its edges privatized to the exclusion of other claims on the Thames' identity, usage and meaning. Although cognizant of the power of private and property interests and the leverage they may exercise through state mechanisms, this paper interprets London's 'waterspace' policy and planning in a way that rejects interpretations of the river that simplistically foreground the will of capital and global neoliberalism.